(untitled) (Research, Society and Development, 2020)
Introduction: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. In Brazil in 2017, 69,569 new cases were notified, with an incidence rate of 33.5 cases per 100 thousand inhabitants. Abdominal TB can involve several structures, being defined in four forms: tuberculous lymphadenopathy, peritoneal, gastrointestinal and visceral tuberculosis. In this perspective, this study aims to show the main clinical aspects of abdominal TB and how it can be diagnosed through computed tomography (CT). Methodology: This is a bibliographic review of a qualitative approach of an exploratory type in which searches were carried out in the national and international electronic databases in Portuguese and English. Results: In tuberculous lymphadenopathy the main imaging findings are lymph node volumetric enlargement, calcification and lymph node mass formation, whereas in peritoneal TB the main finding is ascites, in gastrointestinal TB, parietal thickening and mesenteric thickening can be observed, and finally visceral TB is seen to increase the size of the organ. Conclusion: CT has advantages over other examinations of diangónstico of this pathology as it examines several abdominal structures concomitantly. This is a curable disease, which if diagnosed early can be instituted the appropriate treatment as soon as possible.